THE PROPERTY IN ISLAM (IMAM MUHAMMAD ABU ZAHRAH’S PERSPECTIVE) - Badrun Syahir; Mustaffa Abdullah (ISLAMICONOMIC: Jurnal Ekonomi Islam, 2017)
Based on an observation through many communities, it is obviously that people are very careless on the possession of property, or even merely to get the advantage from it. They used not to think about, but prefer to neglect, the rightness of owning, the rightness of acquiring and the rightness of spending the property. In their mind is whatever they can gain, irrespective to the ethic and moral on the way of reaching and gaining, is totally belong to them, and they are free to do so ever. It is a very liberal concept of property.As a way of life, Islamic order ruled all aspects of life including the ownership of the property. There many verses of Al Qur’an as well as the teaching of the prophet Muhammad PBUH about the property. But the problem is there are many muslim scholars who has interpreted Al Qur’an on the fact and reality based only, and not due to the core of the mission of Al Qur’an. Not to pick the Qur’an teaching up to the life, or to build up the life depend on the doctrine of Qur’an, as it is ought to.Imam Muhammad Abu Zahrah, the famous and prominent Egyptian muslim scholar in the first twentieth century who has great intention and desire of the implementation of Islamic law was one who has keen interest on the issue of economy, especially on the issue of usury (riba). He has written several articles, papers and a book as well, on the subject of riba. Moreover, he has also written a set of Qur’anic Interpretation (Tafsiir) in which he commented on some verses concerning the property and wealth.